[OP.LB01.05] AUTOMATED INTERPRETATION OF HOME BLOOD PRESSURE MEASUREMENTS WITH WIRELESS BLOOD PRESSURE MONITOR AND HY-RESULT SOFTWARE: A USER PERCEPTION STUDY. (September 2016) - Postel-Vinay, N.; Bobrie, G.; Steichen, O.; Savard, S.; Persu, A.; Brouard, B.; Vegreville, M.
Abstract : Objective: Hy-Result is a software designed to help patients to: i) comply with the home blood pressure (BP) measurement protocol (the software does not provide results before having 42 BP readings (3 in the morning and 3 in the evening, during 5 to 7 days, and it sends reminders to the users to increase and complete their measurement); ii) self-interpret their results. The validation study was published in 2015 (www.hy-result.com ). We evaluate here the user's perception. Design and method: In March 2016, a questionnaire was sent to 3000 patients using Hy-Result embedded in a mobile app (Health Mate) connected with a wireless BP monitor (Withings BP 800). Population: 228 users (7.6%; mean age 48 ± 13 years) responded to an online self-questionnaire. Results: Ergonomy and understanding: 95% of responders find easy or very easy to understand text messages; 79% declare easy or very easy to send results through pdf report; 80 % agree that the recommendations given by Hy-Result are adapted to their situation; 85 % agree that Hy-Result helps them understand their blood pressure readings. Compliance to self measurement protocol: 88% of responders declare the reminder functionality of measurements useful; 68% accept to get a calendar reminder to check again their BP in several months as suggested by the system. Communication with the health care provider. 67% of responders agree that the software may help when talking with their physician about their BP values. Only 1% state that the software may cause difficulties in this situation 32% neither; 23% actually shared their report with their physician. In this subgroup, 73% declare that their physician thinks Hy-Result is a useful tool (for 26% the physician did not look the report). In one case, the physician advised the patient to stop using Hy-Result. Further use: 75% of the responders declare that they will continue to use Hy-Result (15% do not know, and 10% will stop); 61% will recommend Hy-Result to their family. Limitation: Responder bias Conclusions: The Hy-Result software embedded in the Withings wireless BP monitor is well accepted by the majority of responders to this survey.